Toward More Efficient and More Secure Last Mile Smart Metering and Smart Lighting Communication Systems with the Use of PLC/RF Hybrid Technology. (5th October 2015) - Kiedrowski, Piotr
Abstract : This paper describes the last mile communication system solutions realized in PLC/RF hybrid technology, which is dedicated to Smart Grid communication subsystems, mainly for Smart Metering and Smart Lighting applications. The use of hybrid technology makes the system more efficient and more secure (still being of low cost, in terms of both implementation and operation). This paper proposes a novel parameter, PDR, to describe the performance of the communications in the last mile network. The communications are realized with the use of the narrowband power line communications technique, the low power wireless communications technique, and the combination of them. The cost analysis for the proposed solution is also done. Theoretical considerations, contained in the paper, are the result of the author's experience in the design, implementation, and operation of the last mile Smart Grid communication systems, realized in the narrowband PLC or 433/868 MHz radio technology. These communication systems were developed for data acquisition and distribution between specific terminals, which are Smart Meters or Smart Lanterns. The aim of this paper is to outline superiorities of the hybrid technology, from which the most important is a low layer protection of the sensitive critical infrastructure, which undoubtedly is a last mile Smart Grid communication network.